2019
DOI: 10.20546/ijcmas.2019.811.201
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Brucellosis in Bovine

Abstract: Bovine Brucellosis is an infectious disease caused by Brucella abortus. It is a small, nonmotile, coccobacilli, Gram negative, facultative, intracellular bacterial organisms of the genus Brucella. Brucella is named after Sir David Bruce who, in 1886, first isolated the organisms from the spleen of a soldier at postmortem with what was then called Malta fever. The isolation of B. abortus from aborted cattle was carried out by Bang in 1897 (Mcmahan, 1944). The disease has a considerable impact on human and anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…However, molecular characterization revealed higher prevalence of B. abortus in seropositive animals. Contrary to our findings, studies conducted in different parts of the world showed higher prevalence rates of bovine brucellosis like 14.3% in Jimma zone, Ethiopia [ 31 ], 16.3% in southwestern Nigeria [ 32 ], 28.9% in Rwanda [ 33 ],, 55% in 6 southern districts of Albania [ 34 ], 20.36% in India [ 35 ], 31% in Bahr el Ghazal region of South Sudan [ 36 ], and 27.07% in Goa, India [ 37 ]. However, lower prevalence rates had also been reported in some other countries such as 2.4% in Alage district of Ethiopia [ 38 ], 3.40% in Ngaoundéré, Cameroon [ 39 ], 9.7% in Nechisar National Park, Ethiopia [ 40 ], 0.4% in Sendafa, Oromia Special Zone, Ethiopia [ 41 ], 6.35% in Southern Cameron [ 42 ], and 5.10% in Indonesia [ 43 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However, molecular characterization revealed higher prevalence of B. abortus in seropositive animals. Contrary to our findings, studies conducted in different parts of the world showed higher prevalence rates of bovine brucellosis like 14.3% in Jimma zone, Ethiopia [ 31 ], 16.3% in southwestern Nigeria [ 32 ], 28.9% in Rwanda [ 33 ],, 55% in 6 southern districts of Albania [ 34 ], 20.36% in India [ 35 ], 31% in Bahr el Ghazal region of South Sudan [ 36 ], and 27.07% in Goa, India [ 37 ]. However, lower prevalence rates had also been reported in some other countries such as 2.4% in Alage district of Ethiopia [ 38 ], 3.40% in Ngaoundéré, Cameroon [ 39 ], 9.7% in Nechisar National Park, Ethiopia [ 40 ], 0.4% in Sendafa, Oromia Special Zone, Ethiopia [ 41 ], 6.35% in Southern Cameron [ 42 ], and 5.10% in Indonesia [ 43 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Hygromas, usually involving leg joints, are a common manifestation of bovine brucellosis and may be the only pathognomonic sign of the infection [19]. The clinical manifestations most commonly encountered in humans are relapsing fever, fatigue, malaise, chills, sweats, headaches, myalgia, arthralgia, and weight loss [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, brucellosis was categorized under tier one zoonotic diseases [ 34 , 35 ]. The disease is known to be an endemic [ 25 ] and a growing problem in domestic livestock herds in Ethiopia [ 19 ] causing significant loss of productivity through abortion, prolonged calving, kidding, or lambing interval, low herd fertility, and comparatively low milk production in farm animals [ 36 ], as well as chronic and febrile illness in humans [ 37 ]. An initiative called GHSA addressed the burden of zoonotic diseases like brucellosis and planned to eliminate the disease in five years (between 2017 and 2022) [ 34 ].…”
Section: Introductionmentioning
confidence: 99%